Kualitas Pelayanan Perusahaan Daerah Air Minum (PDAM) Kabupaten Bombana - Pratama, Santi Sistra; Kambolong, Makmur; Taufik, Taufik (REZ PUBLICA, 2020)
The purpose of this study is to determine and describe the service quality of Bombana Regional Water Company, state-owned company that facilitates and meets the needs of clean water for Bombana regency community. The problems of this research are 1) Water Pipe Channels that minimize water flow outflow and poor water quality due to brown and sandy, 2) lack of responsiveness of PDAM in overcoming problems, 3) PDAM lack social networking and social media that match the lack of information that customers get. This research uses qualitative method with descriptive approach. Indicators in public service are Tangibles, Reability, Responsiveness, Assurance, and Emphaty. The result of this research is that Regional Water Company Bombana Regency still needs to be improved in terms of things and services, facilities and infrastructure that are still available and services that are still less satisfactory in the service.